Shaping Social Literacy at Distance Lessons by Using Multimedia Technologies - T. I. Zakharova; D. V. Vilkova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies innovation methods of distance interaction in education. The necessity to pass over to distance learning was caused by global pandemic. On March 11, 2020 the WHO called the outbreak of COVID-19 a pandemic, which drastically changed traditional mode of life, business and education all over the world. The demand for learning became more acute. For millions of people distance communications were the only link with the outer world. The need and necessity in distance access to school, secondary and higher education affected the development of new trends in the field of education. The change-over to distance learning in schools and universities requires application of different methods of involving schoolchildren and students in the process of learning and improving skills of independent thinking. The authors provided a number of recommendations dealing with multimedia technology application in distance learning, which aimed at the development of cognitive, communicative skills and skills of logical, creative and critical thinking and social literacy.